Association of intercellular adhesion molecule 1 with the multichain high-affinity interleukin 2 receptor. - Burton, J (1990)
Previously, using flow cytometric resonance energy transfer and lateral diffusion measurements, we demonstrated that a 95-kDa protein identified by two monoclonal antibodies (OKT27 and OKT27b) interacts physically with the 55-kDa alpha protein of the high-affinity interleukin 2 (IL-2) receptor. In the present study, this 95-kDa protein (p95) was purified and amino acid sequence data were obtained that showed strong homology to the human intercellular adhesion molecule 1 (ICAM-1). The identity of the p95 protein with ICAM-1 was confirmed by sequential immunoprecipitations using OKT27 and an antibody, WEHI-CAM-1, that is directed toward ICAM-1. We confirmed the physical proximity of p95/ICAM-1 to the IL-2 receptor alpha subunit by demonstrating that radiolabeled IL-2 could be cross-linked to this protein expressed on activated T cells. In functional studies, the antibodies OKT27 and OKT27b inhibited T-cell proliferative responses to OKT3, to soluble antigen, and to heterologous cells (mixed lymphocyte reaction). However, these antibodies did not inhibit IL-2-induced proliferation of an IL-2-dependent T-cell line. Taken together with our previous observations, the present studies suggest that ICAM-1 is in proximity and interacts physically with the high-affinity IL-2 receptor. The association of ICAM-1 with the IL-2 receptor may facilitate the paracrine IL-2-mediated stimulation of T cells expressing IL-2 receptors by augmenting homotypic T-T-cell interaction, by receptor-directed focusing of IL-2 release by helper T cells, and by focusing IL-2 receptors of the physically linked cells to the site of lymphocyte function-associated antigen 1-ICAM-1-IL-2 receptor interaction.